Effect Model (SAVI) in Mental Habits of Fourth Year Middle School Students in Biology - Salman, Zeina Ahmed; Ghada Sharif Abdel (South Eastern European Journal of Public Health, 2024)
The research aims to identifymodel (SAVI) inmental habits forFourth year middle school students in biology. The researcher randomly selected Al-Tahrir Government Girls’ Day Secondary School in the center of Babil Governorate, as the school contains four classes for the fourth year of middle school and includes (155) students distributed in order.(38 - 39 - 40 - 38) in four sections (A - B - C - D)AndBy random drawing, Section D represented the experimental group, which would study biology according to(SAVI model) and division (b) represents The control group will study the same material in the usual wayThe total number of female students in both groups was:After exclusion(70) Reality student (35) female students in each group,The researcher conducted equality between the students of the two research groupstoFor the following variables (chronological age calculated in months, previous information, biology grades for the third intermediate grade, and intelligence test) Auteus LinyonAnd a measure of habits of mindThe research was limited to female students in the fourth year of middle school For the year Academic(2023-2024) for the first semester and the scientific subject specified in the semesters (first - second - third - fourth - fifth) of the biology textbook and after parity between...The two groupsThe researcher prepared the application requirementsFor both groupsAfter completing the experiment, the researcher applied her research tools to...The two groupsI got data It was processed by testing (t-Test) and the results showed that the experimental group outperformed the control group according to a model(SAVI)inHabits of mind.